VIPVIZA VIsualiZation of asymptomatic Atherosclerotic disease for optimum cardiovascular prevention ─ a randomized controlled trial nested in the Västerbotten Intervention Program - Psychological (Problem management) , baseline - Norberg, Margareta; Nordin, Steven; Lindahl, Bernt; Department of Public Health and Clinical Medicine, Umeå University (Umeå University, 2021)
The aim of the project is to develop better methods for prevention of cardiovascular diseases (CVD). It is based on the hypothesis that image-based information on subclinical atherosclerosis (i) increases the precision in the assessment of risk of CVD, (ii) improves communication and understanding of the risk, and as a consequence (iii) the motivation for and adherence to evidence-based pharmacological treatment and lifestyle modification will increase. In addition to conventional risk factor assessment and CVD prevention within the framework of Västerbotten Intervention Program.

3500 healthy participants with low/moderate risk of CVD underwent ultrasound examination of the carotid arteries and were randomized to two groups. In the intervention group, the participants and their doctors received pictorial and graphic information in color about the participant’s subclinical atherosclerosis. No information about the ultrasound results was given to the control group. Follow-up after 1, 3 and 6.5 years includes sampling regarding clinical risk factors, blood for biomarker analyses, extensive questionnaires and interviews.

At 3 and 6.5 years the ultrasound examination was repeated and all participants and their doctors were informed about the results. The database also includes register data regarding prescriptions of preventive medication, exposure data for air pollutants, data from health examinations within the VIP 10 and 20 years before VIPVIZA, and for men conscription data.

After 10 years, registry data on endpoints, CVD morbidity and mortality will be collected.

Access to VIPVIZA's data portal and research data from VIPVIZA is possible in collaboration with researchers within the VIPVIZA project. For further information, contact PI Ulf Näslund ulf.naslund@umu.se

Validated questionnaires on psychological factors of importance for the development of CVD.
Examples: Health literacy, anxiety/depression, coping mechanisms, general self efficacy, optimism/pessimism.
Self-rated risk of CVD and specific self efficacy.

Projektets syfte är att utveckla bättre metoder för prevention av hjärtkärlsjukdom. Den bygger på hypotesen att bildbaserad information om subklinisk åderförkalkning (i) ökar precisionen i bedömningen av risk för hjärtkärlsjukdom, (ii) förbättrar kommunikationen och förståelsen av risken, och som en följd (iii) ökar motivation för och följsamhet till evidensbaserad läkemedelsbehandling och levnadsvaneförändring.

3500 friska deltagare med låg/måttlig risk för hjärtkärlsjukdom har, utöver konventionell riskfaktorbedömning och prevention inom ramen för Västerbottens Hälsoundersökningar, under 2013-2016 genomgått ultraljudsundersökning av halskärlen och randomiserats till två grupper. I interventionsgruppen informerades deltagaren och hens läkare med bild och grafik i färg om individens subkliniska åderförkalkning. Till kontrollgruppen gavs ingen information om ultraljudsresultaten. Uppföljning efter 1, 3 och 6 år omfattar provtagning avseende kliniska riskfaktorer, blodprov för analys av biomarkörer, omfattande enkäter samt intervjuer.

Efter 3 och 6 år upprepades ultraljudsundersökningen och samtliga deltagare och deras läkare informerades om resultatet. I databasen ingår även registerdata avseende förskrivning av läkemedel, exponeringsdata för luftföroreningar, hälsoundersökningsdata 10 och 20 år före ingång i studien, samt för männen mönstringsdata.

Efter 10 år inhämtas registerdata avseende endpoints: insjuknande och död i hjärtkärlsjukdom.

Åtkomst till VIPVIZAs dataportal och forskningsdata från VIPVIZA är möjlig i samarbete med forskare inom VIPVIZA-projektet. För närmare information kontakta PI Ulf Näslund ulf.naslund@umu.se

Validerade instrument avseende psykologiska faktorer av betydelse för utveckling av hjärtkärlsjukdom Exempel: Hälsolitteracitet, ångest/depression, coping mekanismer, generell self efficacy, optimism/pessimism .
Självskattad risk för hjärtkärlsjukdom och specific self efficacy.
VIPVIZA Visualisering av tyst åderförkalkning för effektivare och mer jämlik prevention och minskad förtida död i hjärtkärlsjukdom ─ en randomiserad kontrollerad studie integrerad i rutinsjukvård i Västerbotten - Psykologiska faktorer (Problemhantering), baslinjen
VIPVIZA
Keywords: Biomedical Research; Biomedicinsk forskning; Cardiovascular Diseases; Kardiovaskulära sjukdomar; Primary Prevention; Primärprevention; Ultrasonography; Ultraljudsundersökning; Randomized Controlled Trial; Randomiserad klinisk prövning [Publikationstyp]; Risk Assessment; Riskbedömning; Risk Reduction Behavior; Riskreducerande beteende; Consumer Health Information; Hälsoinformation; plaque; plack; arteriosclerosis; areterioskleros; Cardiology and Cardiovascular Disease; Kardiologi och kardiovaskulära sjukdomar; Radiology and Medical Imaging; Radiologi och bildbehandling; Clinical Laboratory Medicine; Klinisk laboratoriemedicin; General Medicine; Allmänmedicin; Medical Biotechnology (Focus on Cell Biology, (incl. Stem Cell Biology), Molecular Biology, Microbiology, Biochemistry or Biopharmacy); Medicinsk bioteknologi (inriktn. mot cellbiologi (inkl. stamcellsbiologi), molekylärbiologi, mikrobiologi, biokemi eller biofarmaci); Psychology; Psykologi; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin